2022
DOI: 10.3390/bioengineering9110633
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Bioinformatics-Based Subtractive Genomics Approach to Decipher the Therapeutic Drug Target and Its Possible Intervention against Brucellosis

Abstract: Brucella suis, one of the causative agents of brucellosis, is Gram-negative intracellular bacteria that may be found all over the globe and it is a significant facultative zoonotic pathogen found in livestock. It may adapt to a phagocytic environment, reproduce, and develop resistance to harmful environments inside host cells, which is a crucial part of the Brucella life cycle making it a worldwide menace. The molecular underpinnings of Brucella pathogenicity have been substantially elucidated due to comprehen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…The present work applied reverse vaccinology and machine learning strategies to HPV genome and proteome, including both structural and nonstructural viral proteins to predict antigenic peptides. As in vivo screening of enormous vaccine candidates is resource intensive and time consuming [ 28 ]. In contrast to conventional reports our study indicated that nonstructural proteins can also be used for prediction of antigenic peptides.…”
Section: Discussionmentioning
confidence: 99%
“…The present work applied reverse vaccinology and machine learning strategies to HPV genome and proteome, including both structural and nonstructural viral proteins to predict antigenic peptides. As in vivo screening of enormous vaccine candidates is resource intensive and time consuming [ 28 ]. In contrast to conventional reports our study indicated that nonstructural proteins can also be used for prediction of antigenic peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, any existing covalent bonds were managed using the SHAKE algorithm. The CPPTRAJ package was utilized for trajectory analysis, and the simulations were executed using PMEMD.cuda ( Salomon-Ferrer et al, 2013 ; Roe and Cheatham, 2013 ; Khan et al, 2022b ).…”
Section: Methodsmentioning
confidence: 99%
“…Molecular docking was then used to predict the binding affinity and mode of action of a small molecule ligand with a target protein ( Muhammad et al, 2021 ; Hassan et al, 2022a ; Khan et al, 2022 ). The common genes were then docked with target proteins to predict binding affinity among active compounds and target proteins.…”
Section: Methodsmentioning
confidence: 99%